Microsurgical Reconstruction During Covid-19 Pandemic Setting: A Systematic Review and Clinical Applications - Atmodiwirjo, Parintosa; Ramadan, Mohamad Rachadian; Ralena, Nadhira Anindita; Triatmoko, Sara Ester (Jurnal Plastik Rekonstruksi, 2021)
Introduction: The outbreak of the novel coronavirus disease 2019 (COVID-19) has taken almost all countries worldwide. This situation has compromised the safety and health of all medical workers, including microsurgeons. Given that there have been various articles published about the recommendations in microsurgical reconstruction during the COVID-19 pandemic, We felt compelled to compile all relevant studies about the microsurgical reconstruction in the COVID-19 pandemic setting, describe the various actions from different perspectives, as well as providing suggestions based on evidence-based medicine. Method: We did a systematic literature search using electronic databases such as PubMed, Embase, Medline, Wiley, and Cochrane using keywords reconstruction, Microsurgery, coronavirus, and COVID-19. All included studies were critically appraised and reviewed. Results: Nine relevant articles were included for the final review, four of them were qualitative studies, and 5 were guidelines. Studies look at various surgeon's experiences from different healthcare systems during the COVID-19 pandemic. The focuses of the included studies are also diverse from head and neck surgery, breast surgery, limb surgery, and general Reconstructive Microsurgery. Conclusion: Microsurgical reconstruction is not suggested to perform during the peak of the COVID-19 pandemic. It is indicated only if necessary after a rigorous review by the multi-disciplinary team. A full PPE, including a Powered Air Purifying Respirators (PAPR) system, fit-tested N95 respirator masks, face shield, and tight-fitting eye protection goggles, are recommended in performing the surgeries.